An inclusive ontology based on the categories of intelligent software agents: an exploratory research. (20th May 2011) - Farzaneh, Mandana; Vanani, Iman Raeesi; Sohrabi, Babak
The main purpose of this paper is to illustrate a pervasively explored literature-based categorisation of intelligent software agents and present a new taxonomy of them through the definition of ontology for helping and guiding the future research, both in theory and practice, toward coherence. The process of category building has undergone a broad literature review of various related papers and academic works. The aim of the categorisation has been the extraction of an encompassing ontology which covers a wide range of internationally accepted types of agents and their corresponding features in order for the researchers to apply them into the appropriate context as required. Such ontology considerably helps the academic scholars in developing the related literature based on the firm ground provided and it will also contribute to the practitioners in developing multi-agent systems based on the similarities, differences, and cross-functional features and characteristics of intelligent software agents provided in the ontology of agent categories and features.